Synthesis, magnetic and spectroscopic studies of Ni(Ii), Cu(Ii), Zn(Ii) and Cd(Ii) complexes of a newly Schiff Base derived from 5-Bromo-2-Hydroxybezylidene)-3,4,5-Trihydroxybenzohydrazide) - Alhadi, A.A.; Abdullah, M.A.; Ali, Hapipah Mohd; Yehye, W.A.; Shaker, S.A. (2012)
A new hydrazide Shiff base ligand GHL1 (5-bromo-2-hydroxybezylidene)-3,4,5-trihydroxybenzohydrazide) was prepared by refluxing of trihydroxybenzhydrazide with an ethanolic of 5-bromo-2-hydroxybenzaldehyde. The ligand reacted with Ni(II), Cu(II), Zn(II) and Cd(II) (acetate salts). All the complexes were characterized by elemental analysis, molar conductivity, TGA, UV-Vis and FT-IR spectral studies. All the complexes have octahedral geometry except Ni(II) complex which has tetrahedral geometry.